Soil nutrient and invertase-producing bacteria relation impact on Cilembu sweet potato (Ipomoea batatas L.) growth: A study based on upland and wetland cultivation in Cilembu village Sumedang district - Solihin, Eso; Anwar, Syaiful; Santoso, Dwi Andreas; Nugroho, Budi; Purwono, Purwono; Sudirja, Rija; Maulana, Haris; Kamaluddin, Nadia Nuraniya; Karuniawan, Agung (Universitas Padjadjaran, 2023)
The environment is one important factor that must be considered in supporting sweet potato productivity. Environmental factors can be biotic and abiotic, including the availability of nutrients and microbes in the soil. This study aims to identify the nutrient content of the soil in wetland and upland, identify the total invertase microorganisms in wetland and dupland, and identify the relationship between soil nutrients and microorganisms during the growth of Cilembu sweet potato in dry and wetland agroecosystems. This research was conducted on upland and wetland in Cilembu Village, Sumedang Regency. The experimental design used was a single randomized block design (RBD) with six treatments and three replications: A; Rancing, wetland, B; Biang wetland, C; Mencrang wetland, D; Rancing, uplands, E; Biang, uplands, F; Mencrang, upland. Parameters observed included pH, C-organic, total-N, available-P, exchangeable K, exchangeable Na, exchangeable Ca and exchangeable Mg, CEC, and total invertase-producing bacteria. The results showed that in wetland nutrient content such as N, P, exchangeable Ca, Mg, Na, CEC, C-organic and pH tended to be more available. K content and abundance of invertase bacteria are more available in upland. The availability of invertase bacteria has a close relationship with the K content. The information generated in this study can be used as a basis for determining an effective location to produce good quality.